Exploring the causes of Low-Productivity in Dairy Supply Chain using AHP - Rahul S Mor; Sarbjit Singh; Arvind Bhardwaj (Jurnal Teknik Industri, 2017)
Dairy industry is one of the essential global industries with considerably important implications for world economy where the dairy supply chains (DSC) cover every stage of the food system starting from the milk production at farmer level to final consumption. For achieving success in the dairy supply chain, it is needed to focus on critical factors (CFs) that are necessary for an organization to achieve its corporate goals with continually improving the operational performance. In this context, the current study is an attempt to identify the critical factors causing low-productivity in dairy supply chains. After comprehensive literature review and pilot studies in some dairy industries located in northern region of India, a total of 32 critical factors have been identified. A structured questionnaire consisting of 32 CFs have been circulated and the data has been collected from select cooperative dairy units. Further, only eight major critical factors have been carried forward for AHP analysis based on the data collected. The factor having higher weightage score is considered as major CF. The findings of this study indicate that the poor logistics and transportation facilities is the most critical factor as productivity barrier in the context of coop. milk processing units in northern India. This research study would be useful for the dairy professionals & managers of milk processing units to manage their production operations effectively by considering the identified CFs.